Assessing Hand Function in Trans-Radial Amputees Wearing Myoelectric Hands: The Virtual Eggs Test (VET) - M. Controzzi; L. Angelini; P. Randi; P. Mucci; A. Mazzeo; R. Ferrari; E. Gruppioni; C. Cipriani (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
The evaluation of hand function is of great importance to both clinical practice and biomedical research and is frequently evaluated by manual dexterity. Most of the assessment procedures evaluate the gross or the fine dexterity of the hand, but few of them are devoted to the assessment of both. We developed the Virtual Eggs Test (VET): it resembles the task of transporting fragile and robust objects, thus requiring both gross and fine dexterity. The test is composed of 11 Virtual Eggs that collapse if the grasping force exceeds their breaking thresholds, ranging from 0.4 N to 11.5 N. The test aims to transport each Virtual Egg over the barrier in the centre of the test platform without breaking it and as fast as possible. The metrics measured during the test are combined and provide two indexes that evaluate, respectively, gross and fine dexterity. We verify the concurrent validity and the construct validity of the VET with a target population of 30 trans-radial amputees wearing a myoelectric hand and the test-retest reliability on a control population of 35 healthy individuals. The results suggest the ability of the VET to assess hand function specifically in handling breakable objects, using both gross and fine dexterity over time. However, further research is needed to verify its correlation with other tests and the ability of amputees to perform activities of daily living.